2002
DOI: 10.1212/wnl.58.3.471
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis–associated retrovirus (MSRV) in Sardinian MS patients

Abstract: Blood and CSF of Sardinian patients with MS and neurologic control subjects were tested for MS-associated retrovirus (MSRV). CSF detection in MS was 50% at clinical onset, increasing with temporal disease progression, and 40% in control subjects. In blood, MSRV was detected in all MS patients, in most patients with inflammatory neurologic diseases, and rarely in healthy blood donors. MSRV may represent a marker of neurologic diseases of inflammatory origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 12 publications
6
104
1
1
Order By: Relevance
“…Because MSRV was first isolated in choroid plexus/leptomeningeal cell cultures from multiple sclerosis patients (12,13), and virion-associated MSRV RNA can be detected in sera and/or cerebrospinal fluids of such patients (39,40), it is plausible that its envelope protein can exert its CD14/TLR4-dependent proinflammatory effect within the CNS, and therefore initiates and/or substantially exacerbates the disorder. This idea is in line with the findings that: 1) HERV-W ENV and GAG glycoproteins are expressed in the white matter of patients with multiple sclerosis (41)(42)(43), and that 2) the virus load detected in the CSF increases with MS progression and thus may have prognosis value (38).…”
Section: Discussionmentioning
confidence: 99%
“…Because MSRV was first isolated in choroid plexus/leptomeningeal cell cultures from multiple sclerosis patients (12,13), and virion-associated MSRV RNA can be detected in sera and/or cerebrospinal fluids of such patients (39,40), it is plausible that its envelope protein can exert its CD14/TLR4-dependent proinflammatory effect within the CNS, and therefore initiates and/or substantially exacerbates the disorder. This idea is in line with the findings that: 1) HERV-W ENV and GAG glycoproteins are expressed in the white matter of patients with multiple sclerosis (41)(42)(43), and that 2) the virus load detected in the CSF increases with MS progression and thus may have prognosis value (38).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of HERV-H was detected when specific cell types (mainly B cells) of MS patients were cultivated in vitro (99), and the virus was isolated from a clonal line of leptomeningeal cells from an MS patient (100). Elevated levels of antibodies against HERV-H peptides have been found in the serum and CSF MS patients (101), although a detailed study of MS patients in Sardinia identified HERV-H not only in the CSF of 50% of MS patients, but also in 40% of control patients (102). HERV-H is also occasionally present in synovial fluid of rheumatoid arthritis patients (103).…”
Section: 31mentioning
confidence: 99%
“…In the Sardinian cohort, circulating MSRV was detected in 100% of patients with active MS (but in 33% of MS patients in remitting phase, as reported in Figure 2); moreover, the presence of MSRV particles in spinal fluid was found to parallel temporal and clinical progression of the disease [39].…”
Section: Ms and Herv-wsmentioning
confidence: 77%
“…In another longitudinal study, we showed that natalizumab (a humanized monoclonal antibody indicated for MS patients who have not responded to conventional MS treatments) strongly reduced MSRV/syncytin-1/HERV-W expression, which parallels the clinical benefit of the therapy [49]. All the above data [32,[39][40][41][42][43][44][45]47,49] and data from other groups [37,48] strengthen our hypothesis that the evaluation of MSRV/syncytin/HERV-W expression/release could be considered the first prognostic marker for the individual patient to monitor disease progression and therapy outcome.…”
Section: Ms and Herv-wsmentioning
confidence: 87%
See 1 more Smart Citation